Hygienic Behavior of Stingless Bees (Heterotrigona itama) in Cultivated Colonies in the Imbo Putui Customary Forest - Reni Madila; Novia Gesriantuti; Nofripa Herlina; Nuskan Syarif; Said Faizan Tas’ad (JURNAL BIOS LOGOS, 2025)
One of the important behaviors of stingless bees is hygienic behavior, which includes cleaning the nest from dirt, food scraps, and dead insect carcasses to keep the colony healthy and disease-free. The goal of this study was to determine the type and quantity of waste produced by H. itama in the nest, as well as the time spent by worker bees removing waste from the nest. The research method employed was direct observation and quantitative measurement of three active H. itama colonies. The findings revealed that the trash generated contained carcasses, feces, and food scraps. Feces and food scraps accounted for 89%, with carcasses accounting for 11%. The activity of flinging waste out of the nest decreased during the day due to H. itama's high movement in and out of the nest in search of food, as well as high ambient temperatures. The busiest times for garbage disposal were in the morning (09.10 - 11.10 WIB) and afternoon (13.10 - 16.10 WIB). A clean nest with minimal waste suggests a healthy H. itama colony with good hygiene behaviors. In contrast, a messy nest with much excrement indicates an unhealthy H. itama colony with poor hygiene.